Correlated transport through junction arrays in the small Josephson energy limit: incoherent Cooper-pairs and hot electrons - Jared H Cole; Juha Leppäkangas; Michael Marthaler (New Journal of Physics, 2014)
We study correlated transport in a Josephson junction array for small Josephson energies. In this regime transport is dominated by Cooper-pair hopping, although we observe that quasiparticles can not be neglected. We assume that the energy dissipated by a Cooper-pair is absorbed by the intrinsic impedance of the array. This allows us to formulate explicit Cooper-pair hopping rates without adding any parameters to the system. We show that the current through the array is correlated and crucially, these correlations rely fundamentally on the interplay between the Cooper-pairs and equilibrium quasiparticles.